Comparative Genetics: Synergizing Human and NOD Mouse Studies for Identifying Genetic Causation of Type 1 Diabetes (The Review of Diabetic Studies, 2023)
Although once widely anticipated to unlock how human type 1 diabetes (T1D) develops, extensive study of the nonobese diabetic (NOD) mouse has failed to yield effective treatments for patients with the disease. This has led many to question the usefulness of this animal model. While criticism about the differences between NOD and human T1D is legitimate, in many cases disease in both species results from perturbations modulated by the same genes or different genes that function within the same biological pathways. Like in humans, unusual polymorphisms within an MHC class II molecule contributes the most T1D risk in NOD mice. This insight supports the validity of this model and suggests the NOD has been improperly utilized to study how to cure or prevent disease in patients. Indeed, clinical trials are far from administering T1D therapeutics to humans at the same concentration ranges and pathological states that inhibit disease in NOD mice. Until these obstacles are overcome it is premature to label the NOD mouse a poor surrogate to test agents that cure or prevent T1D. An additional criticism of the NOD mouse is the past difficulty in identifying genes underlying T1D using conventional mapping studies. However, most of the few diabetogenic alleles identified to date appear relevant to the human disorder. This suggests that rather than abandoning genetic studies in NOD mice, future efforts should focus on improving the efficiency with which diabetes susceptibility genes are detected. The current review highlights why the NOD mouse remains a relevant and valuable tool to understand the genes and their interactions that promote autoimmune diabetes and therapeutics that inhibit this disease. It also describes a new range of technologies that will likely transform how the NOD mouse is used to uncover the genetic causes of T1D for years to come.